Magnification Factor in Partial Capacity Design for Multitude Bay Buildings - Andrians Juniawan (Advances in Civil Engineering and Sustainable Architecture, 2019)
Partial capacity design (PCD) is an alternative method to design earthquake-resistant structures. PCD leads to a partial side sway mechanism as its collapse mechanism. Therefore, a magnification factor is applied in designing elastic column (usually perimeter column) in order to make it stronger than the plastic columns. The purpose of this research is to try a proposed magnification factor for buildings with long span. Two concrete buildings located in Surabaya at soft soil, consists of 6- and 10-story, were studied. Each building has 9 spans in the x- and y-directions, each 8 meters in length. The buildings were designed with the same columns dimension. The elastic columns were located in the building perimeter. The buildings were evaluated using non-linear time history analysis which shows that partial side sway mechanism was achieved.